{Silver-rich sulfide mineralization in the northwestern termination of the Western Cycladic Detachment System, at Agios Ioannis Kynigos, Hymittos Mt. (Attica, Greece): A mineralogical, geochemical and stable isotope study} - Stouraiti, C.; Soukis, K.; P. Voudouris; Mavrogonatos, C.; Lozios, S.; Lekkas, S.; Beard, A.; Strauss, H.; D. Palles; Baziotis, I.; Soulamidis, G. (Ore Geology Reviews, 2019)
© 2019 Elsevier B.V. Identification of silver-rich sulfide mineralization in the abandoned mines at northern Hymittos Mt (central Attica, Greece) district has made this region important due to its structural relation to the world-class Lavrion mining district (25 km SE of Hymittos Mt.). At Agios Ioannis Kynigos mine veins of oxidized Fe-Pb-Zn-Ag ore are hosted in mylonitic marbles that were predominantly affected by brittle-ductile deformation associated with the West Cycladic Detachment System. The major sulfides are galena and arsenian pyrite which develop as open-space filling (fractures and vugs), disseminations and veinlets. Galena contains abundant inclusions of Pb-As-Sb-Cu-Ag sulfosalts (tetrahedrite group minerals, bournonite, jalpaite). An unusual silver-rich galena ore i.e from 192 to 1500 ppm Ag, is recorded from the present study, with Ag hosted mainly in Ag-tetrahedrite, acanthite and jalpaite. Compositionally pyrite shows As enrichment and the highest As concentration i.e. up to 3.9 wt% is found in the core of the oscillatory zoned pyrites. Values of $δ$34S of galena are isotopically light (−11.2 to −12.2‰), which suggests a sedimentary component to the ore fluid, that is likely derived from leaching of the meta-sedimentary (calc-mica schists) wall rocks. Carbon and oxygen isotope compositions of ore-stage carbonates show values i.e $δ$13CV-PDB (‰) = −8.2 to −11.7‰ and $δ$18O = 24.3 to 25.9‰ and for the non-mineralized carbonates $δ$13CV-PDB (‰) = +0.33 to 2.52‰ and $δ$18O = 20.8 to 26.1‰. The C and O isotopic composition of the carbonate wall rock distal to the orebody is typical of marine carbonates, whereas hydrothermal carbonates (brown calcite and dolomite) are dominated by an external, light C source. The lowest $δ$13CV-PDB values are recorded from cerussite and correspond to the low temperature supergene alteration from meteoric waters. The homogenized values of $δ$18O in the mineralized carbonates indicate interaction of fluid with host carbonates under a low fluid/rock ratio. The Pb-Zn-Ag mineralization at Agios Ioannis Kynigos bears many similarities with the low-temperature carbonate replacement-style mineralization in Kamariza, Lavrion area. Ore deposition in the northern Hymittos detachment fault is focused in the structurally upper parts of the detachment fault where circulation of meteoric fluids is dominant in the hydrothermal system.
Keywords: Carbon isotopes; Hymittos Mt.; Oxygen isotopes; Sulfide mineralization; Sulfur isotopes; WCDS